2005
DOI: 10.2337/diacare.28.2.398
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Candidate Definitions of the Metabolic Syndrome in Adult Asian Indians

Abstract: OBJECTIVES -We aimed to evaluate eight candidate definitions of the metabolic syndrome (MS) against the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATPIII) definition as the reference for optimally defining MS in adult Asian Indians. RESEARCH DESIGN AND METHODS -We used clinical and biochemical data from our previous cross-sectional epidemiological studies. Candidate definitions of MS were proposed by modifying the NCEP ATPIII definition. These modifications included the following: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 17 publications
7
94
1
Order By: Relevance
“…Moreover, most existing studies of SA have focused on Indians (8,14,17,18,(30)(31)(32) , neglecting other groups of SA. The present work represents one of only a few studies to examine MetS prevalence (and the prevalence of abnormal indicators) in the USA in a large sample of SA Americans of different ethnicities and use the newer suggested cut-offs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most existing studies of SA have focused on Indians (8,14,17,18,(30)(31)(32) , neglecting other groups of SA. The present work represents one of only a few studies to examine MetS prevalence (and the prevalence of abnormal indicators) in the USA in a large sample of SA Americans of different ethnicities and use the newer suggested cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…These prevalences are lower than those recently reported in the USA by Khanna et al (77 %) (18) , similar to those found by Ramachandran et al (41 %) (4) and lower than those observed by Flowers et al and Dodani et al (27 %) (23,33) who also used the harmonized WC cut-offs. Prior to the advent of the new harmonized definition, it had been difficult to compare studies of SA since different researchers used different MetS definitions (1,10,34) , various cut-offs (17,(35)(36)(37) as well as different measures of obesity (WC v. waist-to-hip ratio v. BMI) (12,14,21,38) for MetS.…”
Section: Discussionmentioning
confidence: 99%
“…WC, HDL-C, TG) have the same analytical limitations and also show wide variations in different populations. [41][42][43] In summary, Type 2 diabetes mellitus represents an ideal paradigm for the study of the interplay between obesity and the multiple factors that confer increased risk of developing the metabolic syndrome and cardiovascular disease. In view of the current controversy on the precise definition, criteria for diagnosis and pathophysiology of the metabolic syndrome, 3,43,44 some physicians may have problems with including another criterion for the definition of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…BMI \18.5 (regarded as underweight), 18.5-22.9 (Normal), BMI of 23.0-24.9 (at riskobesity) and C25.0 were regarded as obese [15][16][17].…”
Section: Determination Of Anthropometric Indicesmentioning
confidence: 99%